“Diseño de encapsulamiento del motor de una peletizadora de balanceado para reducir el ruido analizando materiales atenuantes en la empresa Exibal”. - Rafael, Velarde (2020)
ABSTRACT: Noise is one of the most common workplace pollutants. Large numbers of workers are exposed daily to potentially dangerous noise levels for their hearing. In many cases it is technically feasible to control applying acoustic engineering techniques on the generating sources. EXIBAL, is an Ecuadorian company located in the city of Riobamba, which processes harmless balanced foods for minor species in a modern way. In the company there is an electric motor of the balanced pelletizer which is three-phase 75 Hp generating a noise of 91.3 dB that in operation causes discomfort to workers who are in the environment during the workday, this being a risk Physically, it was possible to mitigate by installing an acoustic insulation capsule. In its first prototype, it was possible to reduce 2dB, being composed of 6mm chipboard, down and carpet, therefore it was decided to redesign adding a second encapsulation due to the characteristics and conditions present in the In addition to the engine environment, the textile fibers were exchanged for glass wool, 18 mm polyurethane acoustic panels and chipboard, achieving with these materials a decrease to 76.3 dB, achieving a reduced value of 15 dB, thus allowing compliance with the current regulations Executive decree 2393, which stipulates for an 8-hour day the maximum noise allowed is 85 dB, in addition to p prevent occupational diseases, protecting the health of its workers, avoiding expenses in PPE and controlling the risk from the source.